2022
DOI: 10.3389/fcell.2022.887385
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Prognostic Value, and Functional Mechanism of the KDM5 Family in Pancreatic Cancer

Abstract: Background: The histone lysine demethylase KDM5 family is an important epigenetic state-modifying enzyme family. Increasing evidence supports that epigenetic abnormalities in the KDM5 family are related to multiple cancers in humans. However, the role of the KDM5 family in pancreatic cancer is not clear, and related research is very scarce.Methods: R software, Kaplan–Meier Plotter, cBioPortal, TIMER, LinkedOmics, STRING, Metascape, TISIDB, and the GSCA Lite online tool were utilized for bioinformatics analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Interestingly, KDM2A expression in cancer-associated fibroblast promotes carcinogenesis and inhibition of KDM2A suppress the tumor growth via inhibiting PDL1 expression in breast cancer fibroblast cell lines [ 117 ]. Recent large data base analysis revealed that up-regulation of KDM5A/B/C expression was associated with infiltrating immune cells in pancreatic cancer [ 118 ]. Since the activity of KDM family members regulate tumor immunity, therapeutically targeting these proteins in combination with immune checkpoint inhibitors against pancreatic adenocarcinoma needs investigation.…”
Section: Histone Methylationmentioning
confidence: 99%
“…Interestingly, KDM2A expression in cancer-associated fibroblast promotes carcinogenesis and inhibition of KDM2A suppress the tumor growth via inhibiting PDL1 expression in breast cancer fibroblast cell lines [ 117 ]. Recent large data base analysis revealed that up-regulation of KDM5A/B/C expression was associated with infiltrating immune cells in pancreatic cancer [ 118 ]. Since the activity of KDM family members regulate tumor immunity, therapeutically targeting these proteins in combination with immune checkpoint inhibitors against pancreatic adenocarcinoma needs investigation.…”
Section: Histone Methylationmentioning
confidence: 99%
“…In order to understand the functional mechanism of the detected gene mutations in breast cancer with MRD-positive or MRD-negative, KEGG pathway enrichment analysis was performed based on the Metascape database as described previously ( 15 ). All somatic mutations involved in the 125 and 259 gene from 18 MRD-positive patients or 64-negative patients were included in KEGG enrichment analysis, respectively ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the function of the two long noncoding RNA ASMTL-AS1 and LINC00685 is not fully elucidated, it is established that KDM5D (at Yq11.223) encodes a lysin-specific histone H3 demethylase. It has been shown that KDM5D is downregulated and/or associated with poor survival in different malignancies including colorectal cancer [47], lung cancer [48], pancreatic cancer [49], clear cell renal cell carcinoma [50], and gastric cancer [51]. Pathway analysis of autosomal genes with expression levels correlating to KDM5D in male NB tumors indicated epithelial-mesenchymal transition (EMT) and cell migration as top biological processes (Figure 5).…”
Section: Discussionmentioning
confidence: 99%